2015
DOI: 10.11607/ijp.3994
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Interimplant Distance in Mandibular Overdentures Supported by Two Implants on Patient Satisfaction and Quality of Life

Abstract: This assignment applies to all translations of the Work as well as to preliminary display/posting of the abstract of the accepted article in electronic form before publication. If any changes in authorship (order, deletions, or additions) occur after the manuscript is submitted, agreement by all authors for such changes must be on file with the Publisher. An author's name may be removed only at his/her written request. (Note: Material prepared by employees of the US government in the course of their official d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…11, 29 Marin et al 11 reported that in two implant overdenture cases with more than 22 mm interimplant distance, the deactivation of matrices was more common than the distance <22 mm. These findings are partially in compliance with the result of the present study, as 3i locator attachments 29 mm apart lose their retention more rapidly than other groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11, 29 Marin et al 11 reported that in two implant overdenture cases with more than 22 mm interimplant distance, the deactivation of matrices was more common than the distance <22 mm. These findings are partially in compliance with the result of the present study, as 3i locator attachments 29 mm apart lose their retention more rapidly than other groups.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are partially in compliance with the result of the present study, as 3i locator attachments 29 mm apart lose their retention more rapidly than other groups. In the study conducted by Geckili et al, 29 the influence of interimplant distance on oral health impact profile-14 (OHIP-14) of patients using two implant overdentures were analyzed. They failed to find a positive relationship between OHIP-14 total and interimplant distance.…”
Section: Discussionmentioning
confidence: 99%
“…According to our knowledge, few clinical studies already analysed the relation between implant position and prosthetic maintenance. Their focus was mainly on in vitro research and yielded inconsistent results (Alfadda et al, 2017;Aroso et al, 2016;Bonnet et al, 2008;ELsyad et al, 2018;Geckili et al, 2015;Hong et al, 2012;Kobayashi et al, 2014;Kurtulus & Gurbulak, 2018;Scherer et al, 2014;Srinivasan et al, 2016;Stephens et al, 2014;Sultana et al, 2017). The multidirectional chewing forces and the oral environment complicate the comparison between in vitro and clinical research.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research associated a higher inter-implant distance with a better OHRQoL score (Geckili et al, 2015). On the other hand, other studies found no effect of the inter-implant distance on both the quality of the dentures and the patient satisfaction (Alfadda, Al Amri, Al-Ohali, Al-Hakami, & Al-Madhi, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation